Bones: Alex Delaware #23 - Kellerman, Jonathan (New York : Ballantine Books, 2008)
The anonymous caller has an ominous tone and an unnerving message about something "real dead ... buried in your marsh." The eco-volunteer on the other end of the phone thinks it's a prank, but when a young woman's body turns up in L.A.'s Bird Marsh preserve no one's laughing. And when the bones of more victims surface, homicide detective Milo Sturgis realizes the city's under siege to an insidious killer.
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Psychologists -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction